Requirement of Simultaneous Assessment of Crystal- and Supernatant-Related Entomotoxic Activities of Bacillus thuringiensis Strains for Biocontrol-Product Development - Ronaldo Costa Argôlo-Filho; Robson Luz Costa; Daniele Heloisa Pinheiro; Fábio Mathias Corrêa; Fernando Hercos Valicente; Alan William Vilela Pomella; Leandro Lopes Loguercio (Toxins, 2014)
Bioinsecticides with lower concentrations of endospores/crystals and without loss of efficiency are economically advantageous for pest biocontrol. In addition to Cry proteins, other Bacillus thuringiensis (Bt) toxins in culture supernatants (SN) have biocontrol potential (e.g., Vip3A, Cry1I, Sip1), whereas others are unwanted (β-exotoxins), as they display widespread toxicity across taxa. A strain simultaneously providing distinct toxin activities in crystals and SN would be desirable for bioinsecticides development; however, strains secreting β-exotoxins should be discarded, independently of other useful entomotoxins. Entomotoxicity of crystals and SN from a Brazilian Bt tolworthi strain (Btt01) was tested against Spodoptera frugiperda to assess the potential for biocontrol-product development based on more than one type of toxin/activity. Tests showed that 107 endospores mL−1 caused >80% of larvae mortality, suggesting Btt01 may be used in similar concentrations as those of other Bt-based biopesticides. When it was applied to cornfields, a significant 60% reduction of larvae infestation was observed. However, bioassays with Btt01 SN revealed a thermostable toxic activity. Physicochemical characterization strongly suggests the presence of unwanted β-exotoxins, with isolate-specific temporal variation in its secretion. Knowledge of the temporal pattern of secretion/activity in culture for all forms of toxins produced by a single strain is required to both detect useful activities and avoid the potential lack of identification of undesirable toxins. These findings are discussed in the contexts of commercial Bt product development, advantages of multiple-activity strains, and care and handling recommended for large-scale fermentation systems.